Severe fever with thrombocytopenia syndrome virus was found in Northern Jiangxi Province, China - Hu, Haijun; He, Ying; Chen, Fei; Liu, Zhanbin; Wang, Wei; Yang, Shu; Qian, Ke; Zhan, Zhuan; Guo, Yangping; Li, Hui; Zheng, Weiqing (Frontiers in Microbiology, 2024)
IntroductionSevere fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease discovered in China in 2009. SFTS monitoring has been carried out since 2010 in mainland China. In recent years, human infection with SFTS virus (SFTSV) has frequently been detected in Jiujiang of Jiangxi Province, Central China.MethodsSera of SFTS surveillance cases and samples collected from humans, animals and ticks surrounding the cases were used to detect SFTSV RNA by real-time RT-PCR. SFTSV-positive samples were further subjected to sequencing and analysis of the S, M, and L segments of SFTSV.ResultsFour patients were positive for SFTSV infection. However, the subjects like humans, animals and ticks around the cases were all detected as negative for the virus infection. Phylogenetic analysis of the partial segments revealed that SFTSVs in three patients from Jiujiang were clustered with genotype C4 and C5 on the L and M segment-established phylogenetic tree; however, phylogenetic analysis of the S segment showed that the strains were grouped into genotype J1. These results suggested that the S, M, and L segments of these strains underwent segmental reassortment, which was later supported by recombination signal detection. The reassortment event was detected by at least four methods with a significance level of p value <0.05. In addition, the RDP recombination consensus score (RDPRCS) was greater than 0.40. To avoid poor tree topology support with the partial S, M, and L segments, we further performed analysis of the complete genome of SFTSV. The full-length L, M, and S segment sequences of the strains were consistently clustered into two genotypes, namely the genotype C5 and the genotype C4. The strains belonging to genotype C5 were detected for recombination signal with moderate confidence by all the six methods, with a significance level of p value <0.05 and an RDPRCS of 0.41. The recombination event might have occurred between the minor parent (2011YPQ11, C3/C3/C3) and major parent (SPL053A, J1/ J1/ J1). However, there was no genetic recombination detected in the strains belonging to genotype C4. The event was detected by only two methods with a significance level of p value <0.05.ConclusionTwo genotypes of SFTSVs were identified in Jiujiang City, Jiangxi Province of Central China, and they were genotype C5 and genotype C4. The genotype C5 underwent genetic recombination in this region, with the minor parent of the strain 2011YPQ11 and the major parent of the strain SPL053A.